The Relationship Between Local Government Support with Community Participation in the Implementation of Nonformal Education in Marunggi Village - Silvia Septriani Putri; Vevi Sunarti (Universitas Negeri Padang, 2022)
The background of this research is that community participation in the implementation of education has not run optimally in the village of Marunggi, Kota Pariaman. There is still a lot of non-formal education that has not been implemented and faces many problems. This research is a quantitative type of correlational research. community participation in education is very low, but community participation in education is very important because anything that is produced without involving the community in the whole process will result in a lack of a sense of belonging and responsibility for them to participate in implementing and maintaining the continuity of education. The population in this study were 113 people and the sample in this study were 53 people enrolled in non-formal education programs using the Cluster Random Sampling sampling technique, which is group randomization. The analysis of this research is Pearson product moment correlation. There is a significant relationship between government support for community participation in the implementation of non-formal education in the village of Marunggi Kota Pariaman.Keywords: Village Government Support, Community Participation, Non-formal Education